Applying calcium fluoride and silica particles: A solution to improve color homogeneity of pc-WLEDS - Huu Phuc Dang; Nguyen Thi Phuong Loan; Thanh Tung Nguyen; Sang Dang Ho (Institute of Advanced Engineering and Science, 2021)
This article focuses on enhancing the lighting efficiency of pc-WLEDs, a new and advanced lighting solution that has received lots of attention. To adapt to the demand of modern lighting, the lighting performance of pc-WLEDs must be improved, especially the color homogeneity and luminous flux, two of the most important quality indicators of pc-WLEDs. Through experiments, this article proposes using the scattering enhancement particles (SEPs) such as CaF2 and SiO2 with yellow phosphor Y3Al5O12:Ce3+ in pc-WLEDs configuration. The pc-WLEDs model is created by using the LightTools program and set at 8500 K correlated color temperature, while the experimental results yielded from this simulation will be verified by Mie-scattering theory. The information from this article reveals the scattering coefficients of SEPs at 455 nm and 595 nm wavelengths. Moreover, it is confirmed that the employment of CaF2 is effective in promoting the color but may damage the luminous efficiency if the concentration is too high while the SEP material, SiO2, exhibits high luminous efficiency at all concentration.